2021
DOI: 10.1001/jamanetworkopen.2021.0112
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-First Approach to Characterize DICER1 Pathogenic Variant Prevalence, Penetrance, and Phenotype

Abstract: Key Points Question What are the prevalence, risk, and phenotypic spectrum of individuals with a germline putative loss-of-function (pLOF) variant in DICER1 according to a genome-first approach in a population-scale cohort? Findings In this cohort study, DICER1 pLOF variants were more than twice as common (even after adjustment for relatedness) than previously observed. Malignant tumors were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…It is proposed that a male patient with a thyroid cancer or even a multinodular goiter, especially early in life, should be proposed a search for DICER syndrome [ 40 ], which illustrates the combining effect of the gender bias and of the genetic tumor predisposition. Another study starting from search for DICER1 variants in the population found the same number of thyroid cancers in males and females (one for each sex) among carriers of pathogenic variants [ 41 ].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…It is proposed that a male patient with a thyroid cancer or even a multinodular goiter, especially early in life, should be proposed a search for DICER syndrome [ 40 ], which illustrates the combining effect of the gender bias and of the genetic tumor predisposition. Another study starting from search for DICER1 variants in the population found the same number of thyroid cancers in males and females (one for each sex) among carriers of pathogenic variants [ 41 ].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…( 20 ) demonstrated that poorly differentiated thyroid carcinomas in children and adolescents are strongly associated with DICER1 mutations and are highly aggressive, although in most cases differentiated thyroid carcinomas in DICER1 patients behave in an indolent manner ( 20 ). A genome-first approach study of the DICER1 observed that individuals harbouring putative LOF variants of DICER1 had a significantly stronger association with thyroid cancer and thyroidectomy compared to matched controls without DICER1 variations ( 21 ). These findings suggest considerations of early total thyroidectomy in a DICER1 patient - when goitre is detected - is relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Culturing normal HSPCs with MSCs from these mutant mice resulted in altered hematopoietic cell function and morphology, while normal hematopoiesis ensued after the transplantation of bone marrow HSPCs from the mutant mice into wild-type murine recipients [ 280 ]. In contrast to these murine studies, recent research on the initiation of MDS in humans was not found to be associated with pathogenic germline DICER1 variants [ 281 , 282 ]. Studies by Balderman et al [ 283 ], using a transgenic murine MDS model, further support the concept of an altered bone marrow microenvironment contributing to myeloid skewing during MDS progression.…”
Section: Shifting Human Hsc Heterogeneity With Aging and Clonal Hemat...mentioning
confidence: 98%